Boundedness of Riemann-Liouville Operator from Weighted Sobolev Space to Weighted Lebesgue Space - Kalybay, Aigerim; Oinarov, Ryskul (Eurasian Mathematical Journal, 2021)
In this paper, we obtain a criterion for the boundedness of the Riemann-Liouville fractional integration operator from a weighted Sobolev space to a weighted Lebesgue space.